Samarium Promoted Ni/Al2O3 Catalysts for Syngas Production from Glycerol Pyrolysis - Nor Shahirah, Mohd Nasir; Ayodele, Bamidele V.; Jolius, Gimbun; Cheng, C. K. (Department of Chemical Engineering, Diponegoro University, 2016)
The current paper reports on the kinetics of glycerol reforming over the alumina-supported Ni catalyst that was promoted with rare earth elements. The catalysts were synthesized via wet impregnation method with formulations of 3 wt% Sm-20 wt% Ni/77 wt% Al2O3. The characterizations of all the assynthesized catalysts were carried out, viz. BET specific surface area measurements, thermogravimetri analysis for temperature-programmed calcination studies, FESEM for surface imaging, XRD to obtain diffraction patterns, XRF for elemental analysis, etc.. Reaction studies were performed in a stainless steel fixed bed reactor with reaction temperatures set at 973, 1023 and 1073 K employing weight hourly space velocity (WHSV) of 4.5×104 mL g-1 h-1. Agilent GC with TCD capillary column was used to analyze gas compositions. Results gathered showed that the BET specific surface area was 2.09 m2.g-1 for the unpromoted Ni catalyst while for the promoted catalysts, was 2.68 m2.g-1. Significantly,the BET results were supported by the FESEM images which showed promoted catalysts exhibit smaller particle size compared to the unpromoted catalyst. It can be deduced that the promoter can increase metal dispersion on alumina support, hence decreasing the size of particles. The TGA analysis consistently showed four peaks which represent water removal at temperature 373-463 K, followed by decomposition of nickel nitrate to produce nickel oxide. From reaction results for Sm promotion showed glycerol conversion, XG of 27% which was 7% higher than unpromoted catalyst. The syngas productions were produced from glycerol decomposition and created H2:CO product ratio which always lower than 2.0. The H2:CO product ratio of 3 wt% Sm promoted Ni/Al2O3 catalyst was 1.70 at reaction temperature of 973 K and glycerol partial pressure of 18 kPa and suitable enough for Fischer-Tropsch synthesis.